Computer synthesis of diffractive optical elements for forming 3D images - Durlevich, S.R. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2017)
A method is proposed to compute and synthesize the microrelief of a diffractive optical element to produce a new visual security feature: alternation of two 3D color images when the diffractive element is rotated by 90 degrees. Effective algorithms for computing the micro-relief of an optical element are developed. Optimal parameters of the diffractive optical element are determined using methods of mathematical modeling. Sample optical security elements that produce 3D to 3D visual switch effect when illuminated by white light were manufactured using the electron-beam lithography. The optical elements developed can be replicated using a standard equipment employed for manufacturing security holograms. The new optical security feature is easy to control visually, safely protected against counterfeit, and designed to protect banknotes, documents, ID cards, etc.